The Structure and Development of University Students’ Frustration - Hilmi, Fares (Advances in Social Sciences Research Journal, 2015)
Aim : The goal of the present study was to investigate the frustration structure of university undergraduates, and find out how their frustration changes during their years of study. The psychological concept of a mental state of frustration was employed to identify the reasons, situations or mechanisms that stop students from achieving their learning goals in the university. Tool and Sample: An open-ended questionnaire was developed asking students to mention five different situations or incidents that caused them frustration. A sample of 425 subjects responded to the questionnaire during class hours. Eighty percent of the subjects were females.